Rare disease narratives on social media: A content analysis - Hannah J. Park; Cassidy J. Scott; Hadley Stevens Smith; Monica H. Wojcik (Genetics in Medicine Open)
Purpose: Social media provides an opportunity for the expression of people with rare conditions and may provide valuable insight into lived experiences to inform genomic care. Our objective was to describe the nature and content of rare disease video narratives on social media. Methods: We reviewed content on a short-video-format social media website containing the tags of #raredisease, #raredisorder, or #raredisorders. Two authors independently coded videos for content matter and conducted thematic analysis using a mixed deductive-inductive approach. The demographic characteristics of the content and names of specific rare conditions were documented when available, as were the characteristics of the videos themselves. Results: We reviewed 500 videos created by 299 unique users and identified 6 major themes: Spreading Awareness, Guidance for Others, Intimate View into Life, Interactions with Health care, Responses, and Requests for Support. The video narrators were typically family members or caregivers (50.2%) or the person affected (46.6%); a small percentage were health care professionals (2.2%). People with rare diseases in the video comprised both children (40.6%) and adults (52.6%). A total of 189 rare conditions were mentioned, the most common being Ehler-Danlos syndrome (7.8%), Sanfilippo syndrome (1.8%), and narcolepsy (1.8%). Conclusion: Our data suggest that video-format social media allows community building among people affected by rare conditions. Insights from narratives expressed in this format may contribute to a better understanding of medical experiences in the context of daily life, both positive and negative, fostering empathy and leading to improvements in genomic medicine practice.